2015
DOI: 10.1111/gbi.12171
|View full text |Cite
|
Sign up to set email alerts
|

Limited influence of Si on the preservation of Fe mineral‐encrusted microbial cells during experimental diagenesis

Abstract: The reconstruction of the history of microbial life since its emergence on early Earth is impaired by the difficulty to prove the biogenicity of putative microfossils in the rock record. While most of the oldest rocks on Earth have been exposed to different grades of diagenetic alterations, little is known about how the remains of micro-organisms evolve when exposed to pressure (P) and temperature (T) conditions typical of diagenesis. Using spectroscopy and microscopy, we compared morphological, mineralogical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…The identity and morphology of iron minerals formed by NRFeOx can be influenced by the presence of metal species, such as arsenic (As) or silicon (Si) (Kleinert et al, 2011;Picard et al, 2016). For example, during initial formation, the presence of As can direct mineral formation toward the poorly crystalline Fe(III) mineral ferrihydrite as opposed to more crystalline Fe(III) mineral goethite (Kleinert et al, 2011).…”
Section: Environmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identity and morphology of iron minerals formed by NRFeOx can be influenced by the presence of metal species, such as arsenic (As) or silicon (Si) (Kleinert et al, 2011;Picard et al, 2016). For example, during initial formation, the presence of As can direct mineral formation toward the poorly crystalline Fe(III) mineral ferrihydrite as opposed to more crystalline Fe(III) mineral goethite (Kleinert et al, 2011).…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Arsenic co-precipitated with ferrihydrite could potentially be mobilized upon microbial Fe(III) reduction whereas As-goethite coprecipitates would likely be more stable (Hohmann et al, 2009). This transformation process may be inhibited if minerals are co-precipitated with Si, which has been shown to stabilize phases such as ferrihydrite and goethite (Picard et al, 2016). Repeated redox cycling between oxidizing and reducing conditions can influence the products which form as a result of nitrate-reducing Fe(II) oxidation (Mejia et al, 2016) which may influence the interactions between the minerals and other environmental factors.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…According to microscopic observations of experimentally degraded cyanobacteria (Bartley, 1996), the time required to avoid biological degradation during the lithification process has been estimated to be in the range of days to weeks. Experimental studies have shown that chemical signatures of biomolecules evolve during thermal maturation (Alleon et al, 2017;Bernard, Benzerara, Beyssac, Balan, & Brown, 2015;Gupta et al, 2014;Igisu et al, 2009;Picard, Kappler, Schmid, Quaroni, & Obst, 2015;Picard, Obst, Schmid, Zeitvogel, & Kappler, 2016;Schiffbauer et al, 2012). Biomolecules do not all have the same intrinsic resistance (Tegelaar, de Leeuw, Derenne, & Largeau, 1989;Eglinton & Logan, 1991;Bartley, 1996;Briggs, 1999;Zonneveld, Bockelmann, & Holzwarth, 2007).…”
mentioning
confidence: 99%
“…Having determined in Chapter 2 that mineral-organic associations form rapidly and are stable during mineral structural transformations, a series of experiments subjecting OC associated with varying mineral classes (Mn and Fe oxides, aluminosilicates, carbonates, biogenic silica, etc) to early diagenetic reaction conditions could expand on that work and make it more applicable to understanding sedimentary processes. Picard et al (2016) examined high temperature/pressure effects on preservation of cellular material encrusted in biogenic iron oxides, finding that proteins disappeared in diagenetic treatments but lipids and extracellular polysaccharides were better preserved. However, this study submits samples to more extreme diagenetic conditions without pre-aging the OC and is better designed to address the potential for preservation of biosignatures than assess OC preservation potential more broadly.…”
Section: Linking Short-term and Geological Time Scalesmentioning
confidence: 99%